A Modified Endoscopic Technique with Three Incisions for Rockwood Types III and V Acromioclavicular Joint Dislocation. Issue 2 (14th December 2022) - Huang, Jianming; Huang, Danlei; Wang, Jun; Ye, Zhiyang; Liu, Haoyuan
Abstract : Objective: Acromioclavicular joint dislocation is one of the most common shoulder injuries in young men. With the advancement of minimally invasive technology, arthroscopy of acromioclavicular joint dislocation has been recognized for its good curative effect. This study aimed to explore the technical details and clinical efficacy of a modified minimally invasive endoscopic treatment for acromioclavicular joint dislocation. Methods: Clinical data of patients receiving the three‐incision endoscopic treatment were retrospectively reviewed between July 2013 and July 2019. A total of 72 patients with acromioclavicular joint dislocation of Rockwood type III ( n  = 42) and type V ( n  = 30) were included in this study. Postoperative routine radiography was performed to evaluate acromioclavicular joint reduction and fixation. In addition, functional recovery of the shoulder joint was assessed using the American Shoulder and Elbow Surgeons (ASES) and Constant–Murley scores. Differences between the preoperative and postoperative data were compared using paired t ‐tests. Results: All patients underwent loop plate elastic fixation under endoscopy during 24 to 48 months of follow‐up. Postoperative radiography showed that the acromioclavicular joint achieved anatomical reduction. The ASES score (91.1 ± 4.2) was significantly improved compared to the preoperative ASES score (62.4 ± 3.1) ( t  = 46.65, P  < 0.0001). The Constant–Murley score (93.1 ± 4.6) was also significantly higher than that before the operation (40.7 ± 6.4) ( t  = 56.41, P  < 0.0001). No postoperative complications occurred. During follow‐up, four patients had mild acromioclavicular joint degeneration but no obvious pain symptoms. Conclusion: The modified three‐incision endoscopic technique optimizes the surgical incision, reduces trauma, is minimally invasive, and provides rapid rehabilitation with satisfactory clinical outcomes. Abstract : This study introduced a modified endoscopic three‐incision technique and evaluated the modified technique in treating acromioclavicular joint dislocation. Preoperative marker D approach (1 cm of anterior and inferior acromion), E approach (1 cm of the inferior coracoid tip), and H approach (about 3 cm from distal clavicle) were made. X‐ray film showed that the reduction of the acromioclavicular joint was sound.